Hospital construction and emergency waiting time: Evidence from Nicaragua - Sarah Frohnweiler; Esther Luise Heesemann; Marcello Pérez-Alvarez; Manuel Santos Silva; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2024)
We investigate the impact of a large new public hospital on directly observed waiting times in emergency departments of other public hospitals in Nicaragua. Using a difference-indifferences design, we estimate a significant decrease in waiting time by 42% or 10.1 minutes in nearby hospitals compared to hospitals that are further away. The waiting time reduction is largest for nearby hospitals specialized in maternal and paediatric health, as these services overlap the most with those of the new hospital. Findings remain robust to facility and department controls, outlier exclusion, and alternative treatment definitions. A complementary cost-benefit analysis shows that, in addition to the immediate reduction in opportunity costs, the shorter waiting times can also contribute to a reduction in lost earnings by improving patients' health outcomes. Estimates suggest an amortization period of less than one year.
Keywords: 330; waiting time; healthcare infrastructure; hospital construction; impact evaluation; emergency departments